Expressive Illocutionary Acts on Manchester United Instagram Account - Gunawan, I Kadek Adi; Hikmaharyanti, Putu Desi Anggerina (Humanis; Vol 28 No 1 (2024)DO - 10.24843/JH.2024.v28.i01.p011, 2024)
In this study, we analyzed expressive illocutionary acts in Manchester United Instagram comments, drawing on Searle's framework. Public figures and sports clubs, including Manchester United, leverage Instagram for personal branding and fan interaction. Our research focused on three distinct posts, revealing a spectrum of speech acts. The analysis identified a prevalence of thanking (14%), complaining (26%), complimenting (23%), wishing (20%), and greeting (17%). Notably, complaints stood out, indicating follower dissatisfaction with recent club developments. This underscores the significance of social media platforms in fostering user engagement and communication. The study sheds light on how fans express themselves in written form, contributing to the broader understanding of online interactions and the dynamics of fan-club relationships. As Instagram continues to play a pivotal role in communication, our findings offer insights into the diverse ways users engage with a prominent sports brand like Manchester United on this platform.